Differential expression of CD175 and CA19-9 in pancreatic adenocarcinoma - Jane J. Cheng; Yasuyuki Matsumoto; Gabrielle E. Dombek; Kathryn A. Stackhouse; Ana Sofia Ore; Jonathan N. Glickman; Jamie Heimburg-Molinaro; Richard D. Cummings (Scientific Reports)
Abstract Alterations in protein glycosylation are observed in many solid tumor types leading to formation of tumor-associated carbohydrate antigens (TACAs). The most common TACA is the Tn antigen (CD175), which is a mucin-type O-GalNAc-Ser/Thr/Tyr glycan in membrane and secreted glycoproteins. In addition, two other TACAs are CA19-9 (sialyl-Lewis a), which is used as a prognostic serum marker for pancreatic cancer, and its isomer sialyl-Lewis x (SLex, CD15s), which is overexpressed in many cancer types and associated with metastasis. While CD175 and other TACAs may be expressed by many human carcinomas, little is known about their differential expression patterns in tumors, thus limiting their use as tissue biomarkers or therapeutic targets. Here we address the clinicopathological relevance of the expression of CA19-9, CD15s, and CD175 in pancreatic ductal adenocarcinoma (PDAC) tissues. Semi-quantitative IHC staining with well-defined monoclonal antibodies demonstrates that CD175 is expressed in all PDAC specimens analyzed. Unexpectedly, however, these TACAs are differentially expressed within PDAC specimens and their glycoproteins, but not significantly expressed in adjacent normal tissues. These data provide avenues for novel therapeutic approaches that could combine CD175- and CA19-9-targeting therapies for PDAC patients.